Horticulture Exports from Ghana : A Strategic Study - World Bank (Washington, DC, 2017)
In 2003, the World Bank the Agriculture and Rural Development (ARD) department of the Sustainable Development Network (SDN) of the Africa Region commissioned a Ghana Horticultural Sector Development Study. Later that year, the Horticulture Export and Investment Initiative (HEII) were created as the result of restructuring of the agribusiness support component of the Agriculture Services Sub-sector Investment Programme (AgSSIP). HEII played an important role in reshaping the Ghana horticulture cluster through a series of crucial technical support initiatives and building of a key logistics infrastructure at the Tema seaport. HEII also helped to raise the visibility of the horticulture cluster, which resulted in a renewed interest in the sector both from private investors and donor partners. Five years after the original study, the horticulture cluster in Ghana had moved ahead. Developments in the institutional environment had combined with an evolution both of the businesses and of the product portfolio; international trade had expanded and an increasing population participated in export horticulture supported by infrastructural enhancements. At the same time, the external operating environment had changed: not only are markets dynamic, but there were also new influences from policy and trade agreements. The initial scoping review was carried out in early 2008. The scoping study revealed a picture of mixed health, of some successes but not without difficulties; and it confirmed the need for a plan to take the industry forward. The process of validating the review emphasized the necessity for a wide-ranging review of many different factors in order to build a solid business case for a strategy. The present report is the outcome of this two step process. It is laid out in three parts. Part one report on the initial scoping study. Part two defines the vision and the strategy that was formulated in 2010. Part three is a collection of a number of background papers that were researched and written to provide a foundation for the strategy.